2016
DOI: 10.5603/fm.a2015.0097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quercetin on liver regeneration after liver resection in rats

Abstract: (Folia Morphol 2016; 75, 2: 188-195)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The regenerative process following liver resection may trigger apoptotic pathways, resulting in the activation of apoptotic cells 40 . In addition, the surgical trauma itself can cause oxidative stress and inflammation, which may contribute to cell death and apoptosis 41 , 42 . The previous study showed that apoptotic liver cells were significantly increased in the liver resection group compared with the sham group 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The regenerative process following liver resection may trigger apoptotic pathways, resulting in the activation of apoptotic cells 40 . In addition, the surgical trauma itself can cause oxidative stress and inflammation, which may contribute to cell death and apoptosis 41 , 42 . The previous study showed that apoptotic liver cells were significantly increased in the liver resection group compared with the sham group 43 .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Delayed colonic transit was associated with reduced glial Ca 2+ responses and changes in connexin-43, a member of gap junction proteins, in middle-aged (12 months old) mice. 22 Although reduced enteric glia is also observed in humans, 23,24 detailed mechanisms…”
Section: Overvie W Of the Cellul Ar And Fun C Tional Chang E S With Ag Ementioning
confidence: 99%
“…Delayed colonic transit was associated with reduced glial Ca 2+ responses and changes in connexin‐43, a member of gap junction proteins, in middle‐aged (12 months old) mice 22 . Although reduced enteric glia is also observed in humans, 23,24 detailed mechanisms remain unclear. Surprisingly, a recent report suggests that a subpopulation of enteric neurons, but not glia, originate from mesoderm and during aging these mesoderm‐derived neurons become dominant form of all neurons in the enteric nervous system 25 .…”
Section: Overview Of the Cellular And Functional Changes With Agementioning
confidence: 99%
“…The ageing of the gastrointestinal tract has been studied by many authors and their studies have demonstrated various changes related to its function and morphology. Prior studies have pointed to a significant decrease in myenteric neurons at the level of the esophagus and small and large intestines [5,6]. Some of them have reported that the loss of the neurons in older individuals could be compensated by a corresponding enlargement of the neuronal perikarya and their nuclei [5].…”
mentioning
confidence: 99%
“…Prior studies have pointed to a significant decrease in myenteric neurons at the level of the esophagus and small and large intestines [5,6]. Some of them have reported that the loss of the neurons in older individuals could be compensated by a corresponding enlargement of the neuronal perikarya and their nuclei [5]. Other research has shown a decrease in the overall number of neurons per square cm.…”
mentioning
confidence: 99%